Reappearance of buffalo-origin-like porcine circovirus type 2 strains in swine herds in southern China. (May 2017) - Zhai, S.-L.; Zhou, X.; Lin, T.; Zhang, H.; Wen, X.-H.; Zhou, X.-R.; Jia, C.-L.; Tu, D.; Zhu, X.-L.; Chen, Q.-L.; Wei, W.-K.; Lv, D.-H.
Abstract: Previously, we identified three porcine circovirus type 2 (PCV2) strains in buffalo meat samples from southern China. In this study, we confirmed the reappearance of those buffalo-origin-like PCV2 strains in swine herds in this region, which supported the possible cross-species infection of PCV2 between buffalos and pigs under field conditions.